THE ETCHING OF THE COPPER ALLOYS USED IN AUTOMOTIVE INDUSTRY - Egorova, L.; Khobotova, E.; Larin, V. (Харьковский национальный автомобильно-дорожный университет, 2015)
The pattern of the electrochemical ionization and passivation of Cu 62 Zn brass in chloride solutions with different compositions is studied. It is shown that the electrochemical dissolution of Cu 62 alloy in concentrated chloride solutions is controlled by ionization of the copper component in the alloy. There was studied the selectiveness of Cu 62 Zn brass component dissolution and modification of the alloy surface at electrochemical dissolution in chloride solutions.
ТРАВЛЕНИЕ МЕДНЫХ СПЛАВОВ, ИСПОЛЬЗУЕМЫХ В АВТОМОБИЛЬНОЙ ПРОМЫШЛЕННОСТИ
ТРАВЛЕННЯ МІДНИХ СПЛАВІВ, ЩО ВИКОРИСТОВУЮТЬСЯ В АВТОМОБІЛЬНІЙ ПРОМИСЛОВОСТІ
Keywords: brass; ionization; dissolution medium; dissolution selectiveness; латунь; ионизация; травильный раствор; селективность растворения; іонізація; травильний розчин; селективність розчинення; 621.794.42:546.56